Not All Fluid Collections Are Created Equal: Clinical Course and Outcomes of Pancreatic Pseudocysts and Acute Peripancreatic Fluid Collections Requiring Intervention. Issue 5 (May 2023) - Kim, Kevin T.; Clark, Jaclyn; Ghneim, Mira; Feliciano, David V.; Diaz, Jose J.; Harfouche, Melike
Background: Knowledge on pancreatic pseudocyst (PP) management has mostly involved large database analysis, which limits understanding of a complex and heterogeneous disease. We aimed to review the clinical course and outcomes of PP and acute peripancreatic fluid collections (APFC) that require intervention at 1 high-volume center. Methods: Retrospective review of patients with APFC and PP undergoing drainage (2011-2018) was performed. Patients were divided into groups based on initial intervention: surgical (SR), percutaneous (PC), or endoscopic (EN) drainage. Primary outcome was mortality by initial intervention type. Secondary outcomes included subsequent interventions required, length of stay (LOS), readmission rates, and discharge disposition. Results: Of 88 patients, 40 (46.1%) underwent SR, 40 (44.9%) PC, and 8 (9.0%) EN. No patients in EN group had APACHE II scores>20. Pancreatic necrosis was higher in SR (80.5%) and PC (62.5%) groups ( P = .006). There were no differences in mortality, LOS, or readmission rates. Ten patients in the PC group underwent subsequent surgical intervention, of which 9 were due to bowel ischemia. The PC group was 3.4 times more likely to be discharged to rehabilitation over home when compared to the other 2 groups ( P = .04). Conclusion: Patients undergoing surgical or percutaneous drainage of APFC and PP have a greater burden of illness and more local complications requiring intervention compared to endoscopic drainage. The heterogeneity in presentation of peripancreatic fluid collections in acute pancreatitis must be considered when evaluating the benefits of each intervention.